Rugose Morphotype of Salmonella enterica Serovar Typhimurium ATCC14028 Exhibits Chlorine Resistance and Strong Biofilm Forming Ability - Obe, Tomi; Nannapaneni, Rama; Sharma, Chander Shekhar; Kiess , Aaron (International Journal of Poultry Science, 2018)
Background and Objective: Antibiotic resistance is a major global public health problem and studies have shown that when bacteria adapt to one stress, they can offer that protection to resist other stresses. Therefore, the aim of this study was to examine the ability of Salmonella to adapt to chlorine. Methodology: Salmonella Typhimurium (American Type Culture Collection, ATCC 14028) was tested for its ability to adapt to increasing increment of chlorine starting at 125 ppm in tryptic soy broth (TSB). Salmonella Typhimurium demonstrated an acquired tolerance to chlorine in TSB with adapted cells growing in concentrations up to 600 ppm whereas the non-adapted cells did not grow beyond 500 ppm. Results: After 4 days of incubation, S. typhimurium exposed to sublethal chlorine concentrations displayed a distinct rugose and smooth morphology on tryptic soy agar (TSA) plates incubated at 37°C. The rugose, in contrast to smooth morphology (both adapted and control), showed the ability to form very strong biofilms (p<0.05) in polystyrene microtiter plates at room temperature and 37°C. The antibiotic susceptibility patterns of adapted (rugose and smooth) and control cells were tested using different antibiotics according to the Clinical and Laboratory Standards Institutes (CLSI) guideline. There was only slight difference observed in antibiotics resistance of either adapted cell type as compared to control. Conclusion: The incorrect application of chlorine during cleaning and sanitation could select for adapted Salmonella cells, which may attach strongly to plastic surfaces in a processing facility.